STATUS GIZI ANAK BADUTA (BAWAH DUA TAHUN) DI INDONESIA - Noviati Fuada (JURNAL LITBANG PROVINSI JAWA TENGAH, 2017)
Malnutrition remains a serious problem to child survival, growth and development in several developing countries, including in Indonesia. The childhood malnutrition can affect both physical and intellectual growth. This study was to analyses of early childhood malnutrition status using the classification of nutritional (weight, height, and age). Method: The data were collected from National Based Lines Health Survey (RISKESDAS 2010). Those data were analyzed by chi-squared test with dependent variable nutritional status of children, Independent variable including, height of parents, parent’s occupation, parent’s education, health care utilization, immunization, health of the environment. The total data were 13,315 which were obtained from urban, 7,093 samples and 6,222 samples from rural. The nutritional status with height for age in urban areas was influenced by the following factors, economic status of parents, parental education and parental height (p < 0.05). Risk stunting in poor families amounting to 1,319 times. In Rural area, significantly factors are, parental education and parental height (p < 0,05). dan p = 00, 00). While based on indicators of weight and height there are no significant factors related in urban areas.In rural areas, the nutritional status with weight for height was affected by economic status of parents, with the test shown at p = 0:04. Related factors are more common in the use of indicators height-for-age in urban areas. Strategic planning for early prevention, should monitor the height of chlidhood in month period. To improve, should be based on region.